2019
DOI: 10.1039/c8fo02118j
|View full text |Cite
|
Sign up to set email alerts
|

A high-fat high-sugar diet in adolescent rats impairs social memory and alters chemical markers characteristic of atypical neuroplasticity and parvalbumin interneuron depletion in the medial prefrontal cortex

Abstract: A hypercaloric diet given to adolescent rats induces social memory deficits and reduced neurochemical markers of normal social development.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 107 publications
7
37
0
1
Order By: Relevance
“…Interestingly, we did not see effects of HFHS diet on PV neuron immunoreactivity, PNNs or their colocalisations in regions of the PFC. Previous studies have shown that intermittent daily access to a HFHS diet in rats, which causes binge-like behaviours, reduced PV neuron immunoreactivity and PNNs in the PFC 24,26 , and high fat diets (> 60% fat) have been related to reduced PNNs in the PrL and orbitofrontal cortex in male rats 24 . This finding suggests that diet formulations and administration protocols may have differential effects on PFC PV and PNNs, and also supports studies that have observed distinct cross-species expression patterns of PNNs between mice and rats 62 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Interestingly, we did not see effects of HFHS diet on PV neuron immunoreactivity, PNNs or their colocalisations in regions of the PFC. Previous studies have shown that intermittent daily access to a HFHS diet in rats, which causes binge-like behaviours, reduced PV neuron immunoreactivity and PNNs in the PFC 24,26 , and high fat diets (> 60% fat) have been related to reduced PNNs in the PrL and orbitofrontal cortex in male rats 24 . This finding suggests that diet formulations and administration protocols may have differential effects on PFC PV and PNNs, and also supports studies that have observed distinct cross-species expression patterns of PNNs between mice and rats 62 .…”
Section: Discussionmentioning
confidence: 97%
“…As PV neurons mature and integrate into neural networks in the cortex, the expression of PV-protein and mRNA increases along with distinct electrophysiological properties, and this is also reflected by their increased immunoreactivity and numbers during the process of brain maturation 21,22 . Consumption of high-energy "obesogenic" diets is associated with reduced cortical and hippocampal GABA concentration 23 and decreased PV neuron immunoreactivity in regions of the frontal cortex [24][25][26][27] and hippocampus in rats 25,28 , indicating that PV neurons may be at risk of HFHS diet-induced dysfunction. However, due to the relatively late development of PV neurons in the PFC 17,22 , environmental challenges during early life such as stress or poor nutrition may have pronounced and enduring effects on these neurons that could precipitate the development of neuropsychiatric conditions 29 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Within the PFC, PNNs primarily surround PV FSIs and broadly contribute to neuronal stability [23]. In addition, but not limited to, PNNs protect neurons from oxidative stress [24][25][26], impact cognitive performance and memory [27,28], contribute to the establishment and maintenance of fear memories [29][30][31], and are susceptible to modification following exposure to various substances, including high-fat diets [32,33] and cocaine [21,34]. Recent work by us and others has shown that degradation of PNNs attenuates cocaine-conditioned place preference (cocaine-CPP) and cocaine self-administration [21,[35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…This high-fat, high-sugar (HFHS) or “Western diet” results in spatial memory and learning problems, decreased neuronal resiliency to oxidation or other insults, and reductions in neuroplasticity and brain-derived neurotrophic factor in the hippocampus [38-40]. Further, HFHS diets have been associated with reduced synaptic plasticity in the PFC, and impaired function in the amygdala and HPA axis of adolescents [39, 41].…”
Section: Diet and The Development Of Chronic Painmentioning
confidence: 99%